Students’ higher-order thinking skills in discrete mathematics during covid-19 pandemic - Payadnya, I P A A; Wibawa, K A (Journal of physics. Conference series, 2021)
Mathematics learning in the era of 4.0 must be oriented to the aspects of higher-order thinking skills that important for any mathematics subject including discrete mathematics. The online learning caused Covid-19 pandemic influence many aspects of mathematics learning and skills. The purpose of this study was to analyse students’ higher-order thinking skills in the discrete mathematics subject during COVID-19 Pandemic using Two-Tier Multiple Choice (TTMC) instrument. This research was conducted from March to May 2020. Subjects in this study were 11 students of class IIB of Mathematics Education Study Program Universitas Mahasaraswati Denpasar. This study used descriptive analysis techniques. Data collected through tests, interviews, observations, and documentation. The results of the data analysis showed that the higher-order thinking skills percentage of students with very low categories of 18.18%, low 36.36% and moderate 45.45%. Online learning due to COVID-19 Pandemic also causes the difficulties for students to do group discussion as well as the decrease in student motivation. In contrast, students are more familiar with discrete mathematics concepts in their environment such as graph concepts and can use internet facilities in learning more effectively. Some solutions for the problems occurred are: 1) Using interactive learning, 2) Using Project-Based learning (PBL), 3) Discussing current trends in learning, 4) Demonstrating assertiveness, and establishing learning rules, and 5) Supporting students to get better internet facilities.